State Policy Addressing Illegal Foreign Employment in Poland - Piotrowski, Marek (Olsztyn Economic Journal, 2018)
Foreign employment in the informal sector in Poland has not been thoroughly researched to date, mainly due to the obstacles that are faced by researchers who are attempting to investigate the problem. This article focuses on the employment of foreigners in the informal sector in Poland, and it analyzes legal regulations and practices which aim to prevent illegal employment of foreign nationals. The implementation of a simplified procedure for the employment of foreign nationals was one of the most critical amendments to Poland’s immigration policy in the last decade. This solution was met with considerable approval by Polish employers who submitted more than 780,000 and 1300,000 declarations of intent to employ a foreign worker in 2015 and 2016, respectively. However, the results of the inspections carried out by the National Labor Inspectorate give cause for concern. In 2014, nearly 70% of the foreigners named in the declarations of intent were granted a visa and entered Poland. It should be stressed that only 37% of them were employed by the company that issued the declaration.